ESTADOS EXPULSORES Y SEMIPERSONAS EN LA UNIÓN EUROPEA - Silveira Gorski, Héctor C. (Anales de la Cátedra Francisco Suárez, 2009)
The adoption in June 2008 by the European Parliament of the Directive on Return consolidates the process of involution that human rights have been suffering in the EU since the fear of illegal immigration has developed deep roots in its institutions. While the laws of the eighties regarding foreigners already contained rules governing detention and expulsion, it is not until Directive 2001/40/EC2 that the communitarian policy focused on illegal immigration and the expulsion of migrants begins to take shape. The return measures are, as the European Commission said, “a cornerstone of immigration policy in the EU”. Since then, the barbarism of the internment and detention centres, the erosion of rights, the exclusion and criminalization of foreign migrants, have become the battle flag of the associations defending human rights. The erosion that these laws and expulsion measures are causing to the rights and freedoms and to the Constitutional State and its institutions is immense. The decline and erosion in the rights and freedoms is so great that one can no longer talk about Constitutional States in the EU, but rather about administrative machineries for the internment and deportation, and in this way, about “expelling States”(1), where foreign people are treated as “semi-persons” (2) and even as “non-persons”(3).